PENGARUH INDEPENDENSI, KOMPETENSI, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS PEMERIKSAAN (STUDI PADA BPK RI PERWAKILAN JAWA BARAT) - FERDIANSYAH, FERI (Jurnal Ilmiah Mahasiswa FEB, 2017)
The audit report of public sector plays a crucial role for the administration of  a  good  governance.  This  research is  conducted  at  the representative of  the Indonesian Supreme Audit Board in West Java Province. It aims at examining the simultaneous and partial effect of independence, competence, and time budget pressure on the audit quality. The research population is 92 auditors assigned in the representative office and selected through purposive sampling technique under the criterion of two-year professional experience. The data are collected by means of questionnaire. As many as 42 questionnaires are processed for analysis using a multiple linier regression test by SPSS tool.The result of the study shows that independence and competence partially give positive influence towards the audit quality; meanwhile, time budget pressure give the reversal effect. Above all, the result of simultaneous test indicates that independence, competence, and time budget pressure affect the audit quality.The outcome of this research implies that improving the inspection quality requires enhancement of the inspectors’ competence and independence. The auditor’s  competence  may  be  improved  by  upgrading  their  experience  and knowledge through training and education. The independence can be maintained by protecting the auditor from the pressure of auditees and administering peer review for the routine audits. The improvement of audit quality is also feasible by lowering the time budget pressure. This is a practical step because a high pressure can cause the auditor’s neglecting some important audit programs and, in turn, reduces the assessment quality. Keywords: Independence; Competence; Time Budget Presssure; Audit Quality